IN VITRO SEED GERMINATION AS AN AID TO CONSERVE AERIDES MACULOSUM LINDL., AN ENDEMIC AND ENDANGERED ORCHID OF WESTERN GHATS, INDIA. - SRIVASTAVA DEEPTI; GAYATRI M.C.; SARANGI SITIKANTHA (International Journal of Pharma and Bio Sciences, 2013)
Aerides maculosum Lindl., is an endemic orchid species of Western Ghats, India. In this study, an efficient and reproducible protocol was developed for in vitro seed germination. The seeds were cultured on MSBM supplemented with variable concentrations of coconut water (CW) and 6-BAP, casein hydrolysate (CH) and banana pulp. 87%-91% seeds were found viable by differential staining. MSBM supplemented with 10% CW, 2mg/l 6-BAP and 500mg/l CH exhibited best (95.6%) germination rate. Effect of MSBM in combinations of growth regulators: 1-NAA, IAA 6-BAP, kinetin on protocorm were studied. MSBM fortified with 6-BAP (2mg/l) and 1-NAA (1mg/l), resulted in 3.78±1.81 shoots per plantlet and 2.62±1.68 roots per plantlet. The healthy axenic plants with well developed roots were transferred to peat: perlite: vermiculite (1:1:1v/v) medium for 90 days, followed by the medium brick chips: charcoal: mosses (1:1:1v/v) for six months. The acclimatized plants were reintroduced to the nature with 77% survival frequency.